EVALUASI PENGGUNAAN FILLER TEPUNG SEREAL DAN ASAP CAIR TEMPURUNG KELAPA PADA KUALITAS DAN DAYA SIMPAN SOSIS IKAN TENGIRI - Yulistyani, Ratna (UPN VETERAN JAWA TIMUR, 2011)
The aims of this study to determine the type and concentration of filler material of the cereal flour is best at making tengiri fish sausage terms of quality and power consumers have received and to evaluate the influence of the concentration of liquid smoke to the coconut shell store and the consumer preference on the level of sausage products tengiri . The results showed that the best fillers in the manufacture of fish sausage was tengiri cornmeal (Arjuno varieties) with a concentration of 6%, which has a value of 88% WHC with the appearance test score 3.5; 5.0 smell test; sense of 5.0; color resilience 5.0 and 2.8. Minimum inhibitory concentration of liquid smoke to the bacteria coconut shell fish sausage tengiri contaminants on nutrient broth medium with initial population of 10 5 CFU / ml was 0.25%. Coconut shell liquid smoke is more effective in inhibiting the growth of bacteria in sausage products when combined with cold storage / refrigerator temperature. The use of coconut shell liquid smoke concentration 0.5% for the manufacture of fish sausage tengiri already quite effective in inhibiting the growth of bacteria at refrigerator temperature storage preferably consumers than any other treatment.Keywords: Sausage, smoked coconut liquid, filler flour cereals, fish tengiri